Uruguay : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report, 2022)
Uruguay entered the pandemic with solid institutions and social cohesion but growing macroeconomic imbalances-especially slow economic growth and weak public finances-as the end of the last commodity price boom in 2014 uncovered structural weaknesses. A new government came to power in March 2020 with a mandate to boost growth and restore fiscal sustainability. Legislation setting the foundations for many of the reforms has been passed and implementation is advancing--including on a new fiscal rule, and state-owned enterprise (SOE) and pension reforms.